TQM and market orientation's impact on SMEs' performance - Hadi Abdollahi; Kamal Razm; Hamid Rouin Tan (Management Science Letters)
This paper presents an empirical investigation to study the impact of total quality management (TQM) as well as market orientation on organizational performance on some Iranian small and medium enterprises (SMEs). The study designs a questionnaire in Likert scale and distributes it among some experts in city of Shiraz, Iran. Using structural equation modeling, the study determines that three components of market orientation including intelligence generation, intelligence dissemination, and responsiveness through TQM influences on organizational performance components including financial and non-financial performance as well as efficiency. In addition, TQM components including training, process management, supplier quality management, employee relationships, quality of data and reports and top management commitment influence positively on organizational performance in SMEs.